Dampak Pembelajaran Dalam Jaringan (Daring) terhadap Motivasi Belajar Saat Pandemic di MA Al-Muniroh Ujungpangkah Tahun Pelajaran 2020/2021 - Fatimatuz Zahro; Ahmad Maujuhan Syah (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2021)
Online learning is an alternative that can overcome problems in the conventional learning process during the covid-19 pandemic. This study aims to explain in detail how the condition of students' motivation in online learning during the covid-19 pandemic. Covid-19 has had a significant impact on the education sector. Thus, making students less active in conveying aspirations in their thoughts which will certainly have an impact on boring learning and there are shortcomings in its implementation. This study uses a qualitative approach with the type of phenomenological research. Data collection methods in the form of observation, interviews and documentation. Sources of data used in the form of primary data sources and secondary data sources. The data analysis technique uses data reduction, data presentation (data display), conclusion drawing (verification). The validity check technique uses data source triangulation techniques. The results of this study can be concluded due to the current covid-19 all teaching and learning processes are transferred to online or distance learning. Over time the motivation of some students experienced a setback. Due to the long period of time and the facilities of some students who are not always adequate to support distance learning, this is the reason why some students have difficulty interpreting the material being studied, resulting in low student motivation and decreased grades in learning. Due to virtual learning which makes learning not optimal. It can be seen from the results of the study that the impact of online learning on learning motivation during a pandemic has positive and negative sides that can be taken.